7x-5x-4=7(2x+1)

Simple and best practice solution for 7x-5x-4=7(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-5x-4=7(2x+1) equation:



7x-5x-4=7(2x+1)
We move all terms to the left:
7x-5x-4-(7(2x+1))=0
We add all the numbers together, and all the variables
2x-(7(2x+1))-4=0
We calculate terms in parentheses: -(7(2x+1)), so:
7(2x+1)
We multiply parentheses
14x+7
Back to the equation:
-(14x+7)
We get rid of parentheses
2x-14x-7-4=0
We add all the numbers together, and all the variables
-12x-11=0
We move all terms containing x to the left, all other terms to the right
-12x=11
x=11/-12
x=-11/12

See similar equations:

| 6x-3-8x+7=20 | | -6−3j=-2j | | 3/7z=33 | | -4(x-10)=8 | | 2(4x+8)=-46+54 | | -5c=-6−3c | | 3b−6=3 | | 25=-4x+220 | | X+2(4x-4)=10 | | w=10−w | | 2=10-x | | 14x+16=x+81 | | 5x-(-x+1)=-31 | | -5w−10=-7w+6 | | 11r-32-11=2r+2 | | 2g+3(8+2g)=1-g | | 4x-5=12x+3 | | 6n=-8+8n | | 7x+10-6=0 | | 72-9x=48-x | | 9k=6k+6 | | 8+9q=10q | | 314r2=314 | | 4f+4=16 | | −8b+56=−56 | | 5x+15=3x+12=12x+19 | | -2y+2=2+3y | | 3000+145.50x=5910.00 | | −8b+56=-56 | | 5x=-9x+28 | | 4(3x+5)=-30+5 | | 18y+-y+1=18 |

Equations solver categories